2010
DOI: 10.1682/jrrd.2009.10.0165
|View full text |Cite
|
Sign up to set email alerts
|

At-home training with closed-loop augmented-reality cueing device for improving gait in patients with Parkinson disease

Abstract: Abstract-Shuffling and freezing while walking can impair function in patients with Parkinson disease (PD). Open-loop devices that provide fixed-velocity visual or auditory cues can improve gait but may be unreliable or exacerbate freezing of gait in some patients. We examined the efficacy of a closedloop, accelerometer-driven, wearable, visual-auditory cueing device in 13 patients with PD with off-state gait impairment at baseline and after 2 weeks of twice daily (30 minute duration) at-home use. We measured g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 28 publications
4
94
0
7
Order By: Relevance
“…[33][34][35][36][37] More research and outcome data are warranted in these areas. For older patients, active-play video games have increased reaction time, eye-hand coordination, feelings of success, overall physical activity levels, and social involvement.…”
Section: Active-play Video Games In Therapymentioning
confidence: 99%
“…[33][34][35][36][37] More research and outcome data are warranted in these areas. For older patients, active-play video games have increased reaction time, eye-hand coordination, feelings of success, overall physical activity levels, and social involvement.…”
Section: Active-play Video Games In Therapymentioning
confidence: 99%
“…Studies have shown that PD patients benefit in motor learning from cueing [5]. For example, bright parallel [12] and regular white lines [3] have been used on the walkway to improve gait.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies on autonomous entrainment in patients with PD have found on-line and residual therapeutic effects following training with combined visual and auditory feedback [41,42], Effects of "on" predominant freezing of gait [43], online [44,45] and short-term residual [45] improvement by separate visual feedback, freezing predictability by gait initiation with visual feedback [46], and gait improvement by combined visual and auditory feedback in patients subject to deep brain stimulation [47]. Studies of the effects of visual [38] and auditory [39] autonomous entrainment on patients with multiple sclerosis (MS) have found significant on-line and residual improvement in gait parameters.…”
Section: Transformative Nature Of Autonomous Entrainment Across Neuromentioning
confidence: 99%